2012
DOI: 10.1186/1471-2164-13-113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of diverse CIMMYT maize inbred lines from eastern and southern Africa using single nucleotide polymorphic markers

Abstract: BackgroundKnowledge of germplasm diversity and relationships among elite breeding materials is fundamentally important in crop improvement. We genotyped 450 maize inbred lines developed and/or widely used by CIMMYT breeding programs in both Kenya and Zimbabwe using 1065 SNP markers to (i) investigate population structure and patterns of relationship of the germplasm for better exploitation in breeding programs; (ii) assess the usefulness of SNPs for identifying heterotic groups commonly used by CIMMYT breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
124
8
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(159 citation statements)
references
References 41 publications
24
124
8
3
Order By: Relevance
“…This is in agreement with the results of genetic diversity studies from previous research on maize populations (Semagn et al, 2012;Wen et al, 2012). In addition it has been reported that most variation in maize populations is partitioned within, rather than between populations, because maize is an out-crossing species a factor that lead to reduced population differentiation (Hamrick and Godt 1997).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with the results of genetic diversity studies from previous research on maize populations (Semagn et al, 2012;Wen et al, 2012). In addition it has been reported that most variation in maize populations is partitioned within, rather than between populations, because maize is an out-crossing species a factor that lead to reduced population differentiation (Hamrick and Godt 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Overall mean Roger's genetic distance of 0.353 among pairwise comparisons of inbred lines, with the vast majority (94.2 %) showing distances between 0.300 and 0.400 have been reported (Semagn et al, 2012). This slightly differs from the average distance (0.3012) obtained from the current study.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In Eastern Africa, for instance, 3.9% of the cultivated land is under maize production with grain yields of 700 to 1800 kg /ha as opposed to 7437 kg /ha in the USA . In general, maize in Africa is grown on a small-scale by farmers for local consumption, and yields tend to be low, averaging less than half that of Asia and Latin America (Soboksa et al, 2008;Semagn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The growing number of SNP-based maize genetic diversity studies due to decreasing costs per data point, high throughput application and large abundance of SNPs in the maize genome, do not necessarily presume the absolute supremacy of SNPs over SSRs. A recent study demonstrated the suitability of 1065 SNP markers to group 450 diverse maize inbreds according to their pedigrees using different multivariate methods, but it also showed their failure to clearly distinguish between two main maize heterotic groups (Semagn et al, 2012). Comparing the discriminating power of SSR and SNP markers in assessing maize diversity, Wu et al (2016) indicated that the better genome coverage of SNPs contributed to their better performance.…”
Section: Introductionmentioning
confidence: 99%